Propensity for social surfing among the Russian youth: Regional specificity - I. A. Simonova; O. V. Kruzhkova; I. V. Vorobyeva (Russian State Vocational Pedagogical University, 2021)
Introduction. The phenomenon of social surfing, as a specific mobility strategy, largely determines the life of Y and Z generations, and creates an ambiguous context in terms of threats and opportunities for the formation of life trajectories of Russian youth. This actualised the search for theoretical and methodological foundations of understanding and practical tools for assessing the state of this problem, which, in turn, made it possible to scale this phenomenon in the context of the modern youth environment in Russia.The aim of the present research was to identify the degree of loyalty and potential tendency to use the "social surfing" strategy by the representatives of young people in Russian regions, taking into account the assessment of the approval of gender models of this behaviour strategy.Research methodology, methods and techniques. The methodological framework for describing the phenomenon of social surfing is based on the social topology of M. Castells, the het-erological concept of the rhizome by J. Deleuze and F. Guattari, the philosophy of mobility by J. Urry, Z. Bauman, U. Beck, the theory of transitivity (E. M. Dubovskaya, T. D. Martsinkovskaya, E. A. Kiselev), the studies of the specifics of youth identity and self-realisation in social space (M. C. Schippers, N. Ziegler, M. Loreto Martmez, P. Cumsille, A. K. Vikulov, T. V. Plotnikova and others) and the modern concepts of happiness (M. Argyll, D. A. Leontiev, A. L. Zhuravlev and others) The study was conducted in different regions of Russia (Novosibirsk, Ekaterinburg, Chelyabinsk, Kazan, Ulyanovsk, Glazov) using psychodiagnostic methodology "Propensity to social surfing of young people" developed by the authors. The study involved young people (N = 510 people aged 18-27 years old, among them female - 68 %, male - 32 %).Results and scientific novelty. It was found that 11.2 % of young men and women approve of social surfing, evaluate its behavioural model as positive and allow similar options for choosing their own life trajectory. Comparative analysis revealed significant differences in loyalty to the social surfing strategy among young people living in different regions of the Russian Federation: the greatest loyalty was manifested by the young residents of Ekaterinburg, Glazov, and Kazan, while the residents of Chelyabinsk predominantly demonstrated a negative attitude to this strategy. The respondents showed an unequal attitude towards male and female social surfing models: with a relatively condescending attitude towards the male model, social surfing of women is frowned upon and is associated with weakness and statement. Meanwhile, the approval of the male model of social surfing creates certain risks of marginalisation and value-semantic anomie among young people.The practical significance of the conducted research is due to the potential possibilities of using the data obtained for choosing approaches to work with young people in the conditions of their high mobility, as well as for creating educational and professional trajectories.